A Postcolonial Critique of Amartya Sen's Capability Framework - Comiling, Karl S (Archīum Ateneo, 2014)
This paper is a postcolonial critique of Amartya Sen’s capability framework. This is done through first, a consideration of the positive contributions of the capability framework and then, an examination of its inadequacy. The authors argue that while Sen recognizes the importance of building the capability of the poor and promoting participatory freedom, the kind of development he aspires for cannot be fully reached as long as his approach remains within an individualistic capitalist neoliberal framework. Seminal ideas for a re-conception of postcolonial capability building are then offered.